(untitled) (Philippine Journal of Agricultural Economics, 2018)
Sound management of soil nutrients is necessary in improving the productivity of sugarcane monoculture. Different fertilizers have advantages and limitations, thus, it is imperative to frame out a strategy for the judicious combination of these nutrient sources. This study determined the effect of using organic amendments and microbial inoculant on the energetics and economics of sugarcane production under acid upland soil. Field experiment involving twelve treatments using ’Phil 2004-1011’ sugarcane variety was carried in acid Typic Hapludand soil. The recommended N rate (RRN) was reduced to 75, 50 and 25% with subsequent application of mudpress to satisfy the full N recommendation. Bagasse ash and microbial inoculant were used to supplement the nutrient sources. Reducing the recommended N rate with subsequent application of mudpress, bagasse ash and microbial inoculant produced the highest cane and sugar yield. Application of 25% RRN from inorganic fertilizer + 75% RRN from mudpress + bagasse ash + microbial inoculant had the highest energy efficiency and cane yield per joule. Utilization of 50% RRN IF: 50% RRN MP + BA + MI produced the most sugar yield per joule. Better return on investment and benefit-cost ratio were obtained from the application of 50% RRN from inorganic fertilizer: 50% RRN from mudpress. In conclusion, the combined use of inorganic, organic, and biofertilizers can improve cane yield and energy efficiency. Integrated use of inorganic and organic fertilizers can increase economic efficiency.